Direct writing of graphitic carbon/polydimethylsiloxane bimorph thermal microactuator via two-photon polymerization and laser-induced graphitization - Yu YAMASHITA; Yasuko TANAKA; Tianzhou CHEN; Yoshihiro TAGUCHI; Masaaki HASHIMOTO (Mechanical Engineering Journal)
This paper presents a laser direct writing method for the fabrication of a laser-induced graphitic carbon (LIGC)/polydimethylsiloxane (PDMS) bimorph thermal microactuator via two-photon polymerization (TPP) and laser-induced graphitization (LIG). The fundamental parameters of femtosecond laser dotting, adopted as the writing mode for LIG, were investigated by observing the carbonized surface of the TPP-written PDMS plate using optical, scanning electron, and Raman microscopies. Subsequently, as a proof of concept for the proposed method, the LIGC/PDMS bimorph thermal microactuator was fabricated by modifying the surface of a PDMS microcantilever with a thickness of 25 μm and a length of 280 μm through femtosecond laser dotting. The directly written LIGC/PDMS bimorph thermal microactuator produced repeatable displacements of approximately 20 μm with the temperature rise of 66 ℃. Furthermore, the LIGC/PDMS bimorph microactuator exhibited a displacement of 27 μm at 10 mW and a response speed of 0.05 s in photothermal heating. The proposed direct writing fabrication method based on TPP and LIG demonstrates potential for advancing the development of PDMS-based bimorph photothermal microrobots.